Pemanfaataan Media Sosial Dalam Mengembangkan Pembelajaran Matematika Pada Materi Pecahan di SD Kota Malang - DIANA, RISMA FIRDA (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2022)
Social media develops along with technological developments. Social media users are increasing day by day because social media provides lots of exciting content. One of them is educational content. The use of social media among students must be directed so that it has a positive impact. Fractions are abstract mathematical material. Students still have difficulty understanding the concept of fractions and comparing fractions even though they already understand the concept of whole numbers and comparing real numbers. This research aims to describe the use of social media in developing mathematics learning on fraction material at SDIT Insan Mulia Malang. The research method used is descriptive qualitative. Interviews and documentation studies collected data. The results of the research show that the use of social media in developing mathematics learning on fraction material at SDIT Insan Mulia Malang is a means of displaying student work, as a source of inspiration for designing fraction learning media, as a source of inspiration for designing fun fraction learning, and as a means of sharing activities. Mathematics learning is carried out at SDIT Insan Mulia Malang